Rancang Bangun Diagnosa Penyakit Tropis Pada Anak Dengan Metode Forward Chaining Menggunakan Framework Codeigniter - Indrawati, Putri Wahyuni; Ariyanti, Dyah; Aprilia, Ira (INTRO : Journal Informatika dan Teknik Elektro, 2024)
Indonesia is a country with a tropical climate which has two seasons, namely the rainy season and the dry season. From the climatic conditions that occur in Probolinggo district, especially Tiris sub-district, it is very likely that the people of Tiris sub-district are affected by tropical diseases, especially children, as well as limited working hours or doctor's working hours and the large number of patients who have to queue. Because of this, we need a tool that can diagnose children's illnesses in the form of a system. Application for diagnosing tropical diseases in children which can be used for initial diagnosis in children when they experience disorders in the body. The application will display diagnostic results based on the symptoms experienced by the child at that time. The application was built using the PHP programming language with the CodeIgniter Framework.